An experimental investigation of the effect of long-term, time-dependent proppant embedment on fracture permeability and fracture aperture reduction. (August 2021) - Bandara, K.M.A.S.; Ranjith, P.G.; Haque, A.; Wanniarachchi, W.A.M.; Zheng, W.; Rathnaweera, T.D.
Abstract: The inability to achieve satisfactory production targets from unconventional oil/gas deposits is a foremost concern for many hydraulic fracturing projects. One potential reason for recovery difficulties is the lack of a clear understanding of the severity of proppant damage mechanisms in fractures exposed to extreme reservoir environments. In this comprehensive laboratory-scale experimental analysis, we evaluate the significance of one such proppant damage mechanism: proppant embedment, which occurs in fractures over extended time frames, and its ultimate effect on fracture permeability and the reduction of fracture aperture. The results reveal that a significant reduction of fracture permeability occurred after only 36 h of exposure to confining stresses in uniformly (49%) and partially (29%) proppant-distributed fractures. Importantly, by 144 h, permeability reductions of 92.3% and 54.6% were observed for uniformly- and partially-distributed fractures. However, improved permeability results were obtained for multilayer proppant-distributed fractures. The effect of creep-induced proppant embedment was comprehensively studied. In uniformly and partially proppant-distributed specimens, both elastic and creep deformation dominate the embedment process. However, in multilayer proppant-distributed fractures, the embedment process is predominantly governed by the initial elastic embedment mechanism. CT scanning of uniformly and partially proppant-distributed fractures confirmed the substantial reduction in fracture aperture due to proppant embedment combined with fracture asperity damage. Nevertheless, CT scanning revealed only a minor degree of proppant embedment in multilayer proppant-distributed fractures, although significant proppant-re-arrangement occurs in multilayer proppant packs under high-stress conditions. Importantly, for both following scenarios: (1) high confining pressures (30 MPa) at lower testing times (12 h), and (2) low confining pressures (20 MPa) at longer testing times (144 h), the impact of the presence of either a uniform or partial proppant arrangement is minimal, as both proppant arrangements lead to significantly lower fracture permeability and aperture.